2017
DOI: 10.4025/actascitechnol.v39i2.29167
|View full text |Cite
|
Sign up to set email alerts
|

<b>Co-digestion of crude glycerin associated with cattle manure in biogas production in the State of Paraná, Brazil

Abstract: ABSTRACT. The addition of different concentrations of crude glycerin, associated with cattle manure, on the volumetric production of biogas is analyzed. Different concentrations of crude glycerin (2, 4 and 6% m m -1 ) were added as supplement in anaerobic co-digestion of dairy cattle waste, in laboratory batch biodigesters (3.5 L usable volume). The biodigesters were operated under mesophilic conditions (30ºC), with 30-day hydraulic retention time (HRT). Total solids (TS), volatile solids (VS) and chemical oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
2
1
1
Order By: Relevance
“…Treatment C had the lowest efficiency in COD removal values (Table 3) up to the end of the process, which is different from the report of Pazuch et al (2017), with a value of 68%, but in a anaerobic-digestion process where cattle manure and crude glycerin were used. However, these results are similar to those shown by Nuchdang and Phalakornkule (2012) with values >80% that used anaerobic digestion and co-digestion of glycerol and pig manure.…”
Section: Chemical Oxygen Demand (Cod)contrasting
confidence: 49%
“…Treatment C had the lowest efficiency in COD removal values (Table 3) up to the end of the process, which is different from the report of Pazuch et al (2017), with a value of 68%, but in a anaerobic-digestion process where cattle manure and crude glycerin were used. However, these results are similar to those shown by Nuchdang and Phalakornkule (2012) with values >80% that used anaerobic digestion and co-digestion of glycerol and pig manure.…”
Section: Chemical Oxygen Demand (Cod)contrasting
confidence: 49%
“…[45] Sandriaty et al [46] also reported the emergence of sCOD after the biochemical methane potential test conducted in their experiment. Pazuch et al [47] highlighted the possibility of COD increase during digestion due to the organic load of the substrates. Similarly, Barua and Kalamdhad [48] reported the fluctuations of sCOD in the digestion of untreated WH for 50 days, which led to the highest biogas yield achieved on day 32 of the digestion, during which the sCOD was the highest.…”
Section: Effect Of Co-digestion On Cod Reductionmentioning
confidence: 99%
“…Therefore, it has been stated that the use of renewable fuels, such as biofuels, is one of the strategic alternatives to modify the energy matrix of countries, and the use of biogas for electricity generation is likely to be increasingly fostered in Brazil (Pazuch, 2017). Given this, it can be said that the use of biogas is promising.…”
Section: Biodigesters In Brazilmentioning
confidence: 99%